Myokine Response to High-Intensity Interval vs. Resistance Exercise: An Individual Approach - He, Zihong; Tian, Ye; Valenzuela, Pedro L.; Huang, Chuanye; Zhao, Jiexiu; Hong, Ping; He, Zilin; Yin, Shuhui; Lucia, Alejandro (Frontiers in Physiology, 2018)
Purpose: This study aimed to compare the response to acute exercise of several myokines/hormones involved in metabolic function between two types of training sessions that are growing in popularity for their purported cardiometabolic benefits, high-intensity interval (HIIT) and resistance training (RT). Methods: Seventeen healthy, non-athletic men (23±3 years) participated in this cross-over study. They randomly performed a HIIT (with short (HIIT1) or long (HIIT2) intervals) or a RT session. The concentration of fibroblast-growth factor (FGF)21, follistatin, myostatin, interleukin-15, irisin, ghrelin and peptide YY was measured at baseline and 0, 1, 3, 24, 48 and 72 hours post-exercise. An individual approach was adopted to determine the rate of responsiveness to each specific cytokine and training mode. Results: A significant condition (session type) by time interaction (p=0.004) effect was observed for FGF21, with RT eliciting a greater area under the curve (AUC) concentration than HIIT1 (p=0.02). The AUC for follistatin was significantly greater after HIIT2 compared with RT (p=0.02). Individual responsiveness to all session types ranged between 19–93% depending on the cytokine. However, most subjects (71–100%) responded positively for all cytokines (except for irisin, with only 53% of responders) after 1+ session type. Conclusions: Except for FGF21, our results show no overall differences in the myokine response to HIIT or RT. A considerable individual variability was observed, with some subjects responding to some but not other training session types. Notwithstanding, most responded to at least one training session. Thus, it is mostly the individual response of each subject rather than general recommendations on type of training session (i.e., RT vs HIIT or HIIT subtypes) that must be taken into consideration for maximizing cardiometabolic benefits in the context of personalized exercise prescription.